2022
DOI: 10.1021/acs.langmuir.2c01828
|View full text |Cite
|
Sign up to set email alerts
|

Charge–Dipole Attraction as a Surface Interaction between Water Droplets Immersed in Organic Phases

Abstract: The dynamic behavior of emulsion droplets during their interactions with one another or with solid surfaces plays a paramount role in their ultimate stability in various applications. While the interaction of oil droplets through a surrounding aqueous phase is well understood, recent studies on the interaction of water droplets through a surrounding pure organic phase showed the presence of an unexplained attraction between water droplets at relatively long ranges. In this research study, we propose fixed-surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…When two droplets were driven close enough, they tend to coalesce into one droplet. As for the source of the attraction between water droplets, Afsaneh et al 30 suggested that the attraction originates from the charge−dipole interaction by building a model and fitting data from the published literature. 31 Further research is still demanded.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When two droplets were driven close enough, they tend to coalesce into one droplet. As for the source of the attraction between water droplets, Afsaneh et al 30 suggested that the attraction originates from the charge−dipole interaction by building a model and fitting data from the published literature. 31 Further research is still demanded.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[45][46][47] As the entire EHD printing process was conducted at room temperature and standard atmospheric pressure, we do not anticipate any potential instability caused by such external factors on the droplet profiles after the printing process has been completed. [48,49] This is because the shape of the droplets is determined by the interplay between the interfacial tension, gravitational force, and droplet size. The droplet sizes presented in this work are consistently less than 1 mm, where surface tension forces dominate compared to other external factors such as atmospheric pressure and the gravitational force.…”
Section: Effect Of Pulse Durationmentioning
confidence: 99%
“…The potential of mean force, or effective interaction potential (EIP), between particles (where the term 'particle' encompasses molecules, colloidal particles, and clusters) plays a crucial role in various contexts, such as collision rates [1,2], dispersion stability [3][4][5], ion-ligand association [6,7], particle assembly [8], enrichment and fractionation during hydrothermal transport process [9,10]. Although the EIP acquires distinct names in different situations, the underlying phenomena share common features.…”
Section: Introductionmentioning
confidence: 99%